2022
DOI: 10.3934/dcdss.2021069
|View full text |Cite
|
Sign up to set email alerts
|

A new coupled complex boundary method (CCBM) for an inverse obstacle problem

Abstract: In the present work we introduce and study a new method for solving the inverse obstacle problem. It consists in identifying a perfectly conducting inclusion ω contained in a larger bounded domain Ω via boundary measurements on ∂Ω. In order to solve this problem, we use the coupled complex boundary method (CCBM), originaly proposed in [16]. The new method transforms our inverse problem to a complex boundary problem with a complex Robin boundary condition coupling the Dirichlet and Neumann boundary data. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…To analyze the shape Hessian (30), we will write it into an equivalent expression (see [22,23,24,25,26]) and adapt the method already used in [1,2]. We first introduce the operators L : [53,Sec.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze the shape Hessian (30), we will write it into an equivalent expression (see [22,23,24,25,26]) and adapt the method already used in [1,2]. We first introduce the operators L : [53,Sec.…”
Section: 3mentioning
confidence: 99%
“…In this work, we are primarily interested in solving the free boundary problem (FBP) (1) through the novel application of the so-called coupled complex boundary method or CCBM in solving stationary FBPs through the context of shape optimization. For simplicity of discussion, we will consider the prototypical case of (1) in two spatial dimensions popularly known as the exterior Bernoulli problem wherein f ≡ 0, g ≡ 1, and h = λ, where λ < 0 is a fixed constant in (1). That is, we consider the problem of finding a pair (Ω, u) := (Ω, u(Ω)) that solves the system −∆u = 0 in Ω, u = 1 on Γ, u = 0 and ∂ n u = λ on Σ.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For other reconstruction problems, but without the presence of the advection term, we refer readers, for example, to [17,18,20] for inverse scattering problems and [8,7,13,14] for inverse boundary problems involving the (time-dependent) heat equation. More related studies can also be found in [1,2,3] and the references therein.…”
mentioning
confidence: 98%